Performance, carcase traits and bioeconomicity of sheep weaned at different ages and intensively finished on Massai grass pasture receiving concentrated supplementation - dos Santos Silva, Yasmin; Soares, Maria Alice de Lima; Cavalcante Ribeiro, Pedro Henrique [UNESP]; Emerenciano Neto, João Virgínio; Maia, Marciane da Silva; Rangel, Adriano Henrique do Nascimento; Urbano, Stela Antas (Wiley, 2024)
Intensive finishing on pasture is already accepted as a good nutritional management strategy due to the capacity of enhancing performance without requiring physical confinement infrastructure; however, it is not yet known whether early weaning has beneficial results in this system. The effect of different ages at weaning–42, 56 and 84 days–on the performance, carcase traits and bioeconomicity of Santa Inês lambs intensively finished on Massai grass pasture (Panicum maximum cv. Massai) was evaluated. Fifty-seven lambs were weekly weighed from birth until they reached 30 kg of body weight, when the males (not castrated) were slaughtered and the females incorporated into the herd. It was found that weaning at 42 or 56 days depressed lamb performance, so that animals weaned at 84 days reached slaughter weight 32 days earlier. There was no effect (P > 0.05) on carcase traits and meat cuts, but animals weaned at 84 days were more economically profitable. Weaning Santa Inês sheep at 84 days that will be intensively finished in Massai pasture enhances performance and brings earlier age at slaughter, in addition to positively impacting the economic viability of the production system.
Keywords: Age at slaughter; finishing; intensive pasture finishing‌; lambs; sheep meat